PREDICTION OF THE HYDROCARBON SYSTEM IN EXHUMED BASINS, AND APPLICATION TO THE NW EUROPEAN MARGIN - Doré A.G.; Corcoran D.V.; Scotchman I.C. (My University, 2002)
Uplift, erosion and removal of overburden have profound effects on sedimentary basins and the hydrocarbon systems they contain. These effects are predictable from theory and from observation of explored exhumed basins. Exhumed basins are frequently evaluated in the same way as ‘normal’ subsiding basins, leading to errors and unrealistic expectations. In this paper we discuss the consequences of exhumation in terms of prospect risk analysis, resource estimation, and overall basin characteristics. Exhumation should be taken into account when assigning risk factors used to estimate the probability of discovery for a prospect. In general, exhumation reduces the probability of trapping or sealing hydrocarbons, except where highly ductile seals such as evaporites are present. Exhumation modifies the probability of reservoir in extreme cases; for example, where a unit may have been buried so deeply before uplift that it is no longer an effective reservoir, or where fracturing on uplift may have created an entirely new reservoir. The probability of sourcing or charging is affected by multiple factors, but primarily by the magnitude of the post-exhumation hydrocarbon budget and the efficiency of remigration. Generally gas will predominate as a result of methane liberation from oil, formation water and coal, and because of expansion of gas trapped before uplift. These factors in combination tend to result in gas flushing of exhumed hydrocarbon basins. Compared with a similar prospect in a non-exhumed basin, resource levels of a prospect in an exhumed basin are generally lower. Higher levels of reservoir diagenesis influence the standard parameters used to calculate prospect resources. Porosity, water saturation and net-to-gross ratio are adversely affected, and (as a consequence of all three) lower recovery factors are likely. Hydrostatic or near-hydrostatic fluid pressure gradients (as observed in exhumed NE Atlantic margin basins) will also reduce the recovery factor and, in the case of gas, will adversely affect the formation volume factor. Hydrocarbon systems in exhumed settings show a common set of characteristics. They can include: (1) large, basin-centred gas fields; (2) smaller, peripheral, remigrated oil accumulations; (3) two-phase accumulations; (4) residual oil columns; (5) biodegraded oils; (6) underfilled traps. Many basins on the NE Atlantic seaboard underwent kilometre-scale uplift during Cenozoic time and contain hydrocarbon systems showing the effects of exhumation. This knowledge can constrain risk and resource expectation in further evaluation of these basins, and in unexplored exhumed basins.